Benefit-Cost Analysis for Financial Regulation - Posner, Eric; Weyl, E. Glen (American Economic Review, 2013)
Calls for benefit-cost analysis in rule-making, based on the Dodd-Frank Wall Street Reform Act, have revealed a paucity of work on allocative efficiency in financial markets. We propose three principles to help fill this gap. First, we highlight the need for quantifying the statistical cost of a crisis to trade off the risk of a crisis against loss of growth during good times. Second, we propose a framework quantifying the social value of price discovery, and highlighting which arbitrages are over- and under-supplied from a social perspective. Finally, we distinguish between insurance benefits and gambling-facilitation harms of market completion.